Production Increase of a Peruvian Sleepwear Manufacturer SME through SLP, TPM, Poka Yoke and Work Standardization - Vargas Sanders, Angelica Christel (2023)
Currently, the Peruvian textile sector, especially the MSMEs and SMEs, is affected by several factors that have lowered its productivity. This industry is already dealing with complex markets for a high level of competitiveness and informality. For this reason, it is imperative to counteract these factors internally affecting the companies' operating processes. Most companies, intending to lower costs, seek to hire personnel with a certain level of experience since it is assumed that they would support them in carrying out the work in their position, meaning that the personnel hired are not trained to perform their tasks. Likewise, maintenance is minimized or non-existent, and plants are not adequately organized. All these factors result in a decreased level of productivity. This paper seeks to demonstrate that regular training, planned maintenance, and proper plant layout will reduce the negative effects mentioned above. For this purpose, there are specific tools available that will be mentioned in this article, such as SLP, Autonomous Maintenance and/or Planned Maintenance (TPM), Poka Yoke, and Standardized Work, as they will be implemented for intervention in the production process in a company aimed to manufacture sleepwear, where an increase of 14% in their productivity level was achieved.